Case Report: Pulmonary Vein Isolation as a Tailored Treatment for Recurrent Ventricular Tachycardia During Hemodialysis in a Patient With Right Coronary Artery Chronic Total Occlusion - Cosmin Cojocaru; Cosmin Cojocaru; Adelina Pupăză; Corneliu Iorgulescu; Sebastian Onciul; Sebastian Onciul; Lucian Câlmâc; Radu Vătăşescu; Radu Vătăşescu (Frontiers in Cardiovascular Medicine, 2022)
BackgroundCatheter ablation of the ventricular substrate can reduce ventricular tachycardia (VT) recurrence and mortality in an electrical storm (ES). However, identification and specific treatment of plausible triggers is mandatory and may lead to the resolution of ES.ObjectiveThis case presentation seeks to exemplify how pulmonary vein isolation (PVI) may represent a tailored treatment of ES in cases of ventricular substrate, which only becomes arrhythmogenic during high-rate episodes of paroxysmal atrial fibrillation (PAF).ResultsA 54-year-old male with a history of inferior myocardial infarction (MI) and long-term hemodialysis was referred for repetitive implantable cardioverter-defibrillator (ICD) shocks for apparently scar-related monomorphic VT episodes preceded by PAF initiation strictly during hemodialysis. He had recently undergone ICD implantation for similar episodes of ES preceded by the rapid-ventricular response (RVR) PAF during hemodialysis. The patient had no other history of VTs. Electrocardiogram (EKG) changes occurred exclusively during PAF and suggested functional myocardial ischemia. Coronary angiography demonstrated isolated right coronary artery (RCA) chronic total occlusion (CTO). Cardiac magnetic resonance demonstrated RCA-territory residual myocardial viability and mild LV systolic dysfunction. Surgical revascularization was not feasible due to a history of bilateral above-the-knee post-traumatic amputation and severe calcification of internal mammary (IMA) and radial arteries. Subsequent CTO-percutaneous coronary intervention attempt was unsuccessful. The difficulty of assessing LV-substrate ablation end-points due to the “functional” character of the substrate, which only became arrhythmogenic during hemodialysis-related PAF, was considered. Consequently, PVI was performed rather than VT/VF substrate ablation. Twelve months after PVI, the patient remains free of PAF and VT/VF despite chronic hemodialysis sessions.ConclusionThe ES episodes can be triggered by situational factors, such as RVR-PAF and functional ischemia, during hemodialysis in patients with CTO with otherwise no episodes of VT. Tailored treatment of such factors may lead to long-term VT freedom.